Genetic analysis of the population structure of the rice false smut fungus, Villosiclava virens, in China using microsatellite markers mined from a genome assembly. (14th April 2015) - Jia, Q.; Gu, Q.; Zheng, L.; Hsiang, T.; Luo, C.; Huang, J.
Abstract : Studies on population genetics of Villosiclava virens are limited because of the lack of polymorphic markers. Based on a draft genome sequence of isolate HWD‐2 produced in this study, 20 of 403 potential simple sequence repeats (SSR) loci showed polymorphisms in preliminary screening using eight diverse V. virens isolates. Among polymorphic loci, most of them with tetra‐ to hexanucleotide unit motifs showed higher levels of polymorphism than loci with smaller motifs. After testing with 20 polymorphic SSR markers, the 87 isolates of V. virens from eight populations in China showed a high level of genetic diversity, with each as a unique haplotype. This differs from some previous findings showing little to no genetic variation based on random amplified polymorphic DNA and amplified fragment length polymorphism analyses. Among eight populations from major rice production areas of China, the population from Guangxi province in south China showed the highest levels of polymorphism, which led to the speculation that it might be closer to the centre of origin of this pathogen. The northern, central and eastern populations (Jilin, Liaoning, Hubei, Hunan, Jiangxi and Zhejiang), when considered together as a group, showed significant molecular variation compared to the southern populations (Fujian and Guangxi) (ΦPT  = 0·043, P  =   0·037). A significant relationship (Mantel test, P  =   0·027) but with low correlation ( R 2  = 0·23) was also found between geographic distance and genetic distance. The 20 polymorphic SSR primer pairs designed in this study provide a tool for further research on the population diversity of this emerging fungal pathogen of rice.